Comparative Evaluation Of Fracture Resistance Of Bulk-Fill and Conventional Resin Composites Used For The Restoration Of Endodontically Treated Teeth: An In-Vitro Study - Jamir, Limayanger; Goel, Munish; Kumar, Vijay; Rai, Kulwant; Kumari, Shilpa; Mandotra, Prabhat (Journal of Neonatal Surgery, 2025)
Aim: To compare the fracture resistance of bulk-fill resin composites and conventional resin composites used to restore endodontically treated maxillary premolars. Settings and Design: Academic, invitro study Materials and Methods: After seeking approval from the institutional ethical committee following extracted premolars were selected, disinfected and , divided into six groups (n=15 each). Group 1 was left intact (control); Group 2 received endodontic treatment without restoration (positive control). Groups 3–6 received endodontic treatment and were restored with either bulk-fill (Beautifil Bulk, Prime Restorite) or conventional composites (Beautifil II, Dentsply Spectrum). Standard MOD cavity preparations and root canal procedures were performed. The restorations were done as per the respective manufacturer’s instructions. All specimens were mounted in acrylic and subjected to vertical compressive force using a Universal Testing Machine. Fracture loads were recorded in Newtons (N). Statistical Analysis: Data were analysed using Shapiro-Wilk, ANOVA and Tukey's post hoc test (p < 0.05). Results: The intact group had the highest fracture resistance (1691.06 N), followed by Beautifil Bulk (1546 N), Dentsply Spectrum (1478.93 N), and Prime Restorite (1226.33 N). Beautifil II (755.27 N) and the positive control group (704 N) showed the lowest values. Statistical analysis revealed significant differences among most groups, except between Beautifil II and the positive control, suggesting limited reinforcement from Beautifil II. Conclusion: Bulk-fill composites, especially Beautifil Bulk, significantly enhance the fracture resistance of ETTs and offer clinical advantages over conventional composites in terms of ease of application and reduced treatment time. These materials represent a promising solution for posterior restorations where high load resistance is required.